2013
DOI: 10.1128/aem.03040-13
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Adenosine Transferase (KsgA) Deficiency in Salmonella enterica Serovar Enteritidis Confers Susceptibility to High Osmolarity and Virulence Attenuation in Chickens

Abstract: bDimethyl adenosine transferase (KsgA) performs diverse roles in bacteria, including ribosomal maturation and DNA mismatch repair, and synthesis of KsgA is responsive to antibiotics and cold temperature. We previously showed that a ksgA mutation in Salmonella enterica serovar Enteritidis results in impaired invasiveness in human and avian epithelial cells. In this study, we tested the virulence of a ksgA mutant (the ksgA::Tn5 mutant) of S. Enteritidis in orally challenged 1-day-old chickens. The ksgA:: Tn5 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…KsgA is a methyltransferase that dimethylates A1518 and A1519 of 16S rRNA. KsgA deficiency has pleiotropic effects, including resistance to kasugamycin killing (27), increased susceptibility to cold stress and oxidative stress (20), and compromised virulence (20,41). In addition, KsgA deficiency was found to increase the sensitivities to inhibition by kanamycin, gentamicin, and paromomycin, as demonstrated by the MIC 50 s (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KsgA is a methyltransferase that dimethylates A1518 and A1519 of 16S rRNA. KsgA deficiency has pleiotropic effects, including resistance to kasugamycin killing (27), increased susceptibility to cold stress and oxidative stress (20), and compromised virulence (20,41). In addition, KsgA deficiency was found to increase the sensitivities to inhibition by kanamycin, gentamicin, and paromomycin, as demonstrated by the MIC 50 s (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the important role of KsgA during aminoglycoside killing raises the possibility of developing a KsgA inhibitor as a potentiator for aminoglycoside chemotherapy against bacterial infection. An additional advantage of such a potentiator might be that it disarms the virulence of pathogenic bacteria, including Salmonella enterica serovar Enteritidis (20), Yersinia pseudotuberculosis (45), Staphylococcus aureus (41), and A. baumannii, a WHO priority 1 pathogen for new antibiotic development. Thus, such a potentiator might have the ability to "kill two birds with one stone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that some of the pairs of orthologs have higher expression levels in response to drought, including qm9540 (Sinha et al, ), qm3901 (Scharf et al, ), qm27995 (Sun et al, ), qm20708 (Luo et al, ), qm8971 (Giarola et al, ), and qm13577 (Padma et al, ). In particular, one positively selected gene (qm16912), which is related to the response to cold (Chiok et al, ), showed higher expression levels in Q. mongolica compared with Q. liaotungensis . This could provide an insight into the origin of the differences between Q. mongolica and Q. liaotungensis .…”
Section: Discussionmentioning
confidence: 99%
“…The ribosomal maturation factor ksgA is under investigation in our laboratory for its contribution to pathogenicity in chickens. We have previously reported that inactivation of ksgA in SE results in reduced invasiveness in chicken liver cells (Shah et al, 2012b) and impaired intestinal and internal organ colonization in orally inoculated day-old chickens (Chiok et al, 2013). One study identified a few SE-specific genetic factors (SEN1001, SEN1140, SEN1970-SEN1999, and SEN4290-SEN4292) that contribute to pathogenicity in mice, but their role remains to be tested in a chicken model (Silva et al, 2012;Vishwakarma et al, 2012).…”
Section: Genetic Basis Of Gastrointestinal Infection In Chickensmentioning
confidence: 99%